Aplikasi E-Task Berbasis Student Center Learning Pada Matakuliah Manajemen Proyek Sistem Informasi - Sri Restu Ningsih; Ade Irma Suryani; Prima Aulia (Techno.Com, 2019)
At present, there are still many colleges that use Teacher Center Learning (TCL) based learning models. And this has resulted in the low interest of students in following the learning process. The result of the above problem is the decline in student learning outcomes. This study aims to develop a learning media based on Student Center Learning (SCL), by using an E-Task application that can improve students' results and independence in Information Systems Project Management subjects. Where in this case the student will use the E-Task application in working on assignments given by Lecturers independently or in groups, so that in terms of increasing student independence. This research uses the basic concept of system development life cycle (SDLC) system development which is described by the UML system design tool. The designed system flow is illustrated by global design, namely Use Case Diagram. The final result of this research is an E-Task application that is designed attractively so that students are expected to be able to independently carry out their duties and give their assignments to Lecturers anywhere and anytime. With this application students are able to actively work together, so that assignments given to students can be completed quickly, and this application can improve student learning outcomes.